Union Strength of different restoring materials indicated for pediatric dental dentin in deciduous molars - In Vitro Study (Research, Society and Development, 2022)
With the advancement of dentistry, professionals are increasingly looking for restorative materials with good properties, which facilitate the execution of the procedure and establish the longevity of the treatment. Numerous restorative materials are present in dental practice from amalgam to the emergence of esthetic restorative materials. The concern with the adhesion of these materials is present in the clinical practice of pediatric dentistry, due to the small structure of the deciduous tooth, which hinders the longevity of restorations. The aim of this study was to evaluate the bond strength by means of push-out between three restorative materials - Alkasite Resin, Bulkfill Flow Composite Resin and Resin Modified Glass Ionomer Cement - indicated in Pediatric Dentistry, in dentin of primary molars. In this work, a randomized, blind (examiner) in vitro study was carried out, in which cavities were prepared in 18 deciduous molars and filled with different restorative materials: GRA - Alkasite resin with light curing (n=6); GCIV - Resin-Modified Glass Ionomer Cement (n=6); GRB - Bulkfill Flow Composite Resin (n=6). The push-out test was used to evaluate the bond strength. The analysis of variance showed a significant difference between the restorative materials (p=0.007). Thus, we conclude that the bond strength to dentin of primary molars using bulkfill flow resin is superior to the restorative materials tested and that between resin-modified glass ionomer cement and alkasite resin, there is no significant difference in result.